Analysing of Students’ Translation Skill through Idiomatic Translation Method - Puspita, Nurul; Pratiwi, Wiwied; Mahmudah, Masrurotul; Ambariyani, Ambariyani; Arifin, Zainal (Attractive : Innovative Education Journal, 2020)
The aim of this study is to know the level of readability of students’ result translation and the error using translation procedure. The researcher used qualitative research. The subject of this research was 15 students at the fifth semester. The result show that the percentages of students’ idiomatic translation result in readability aspect were; 14% data of the translation result was readable, 59% data of the translation result was almost readable, and 27% data of the translation result was unreadable. The percentage of students done mistake in procedures of translation were: 70% students’ errors in using addition, 60% students’ error in using omission, and 40% student’s error in using transposition. Mostly and relatively they translated the text literally, using unacceptable term, translated out of the context